Аленушкины сказки: рассказы / Дмитрий Мамин-Сибиряк - Мамин-Сибиряк Дмитрий Наркисович (ЭКСМО, 2007)
Экземпляры: ф.3 (20230801) / Инвентарный номер: 63799 / Цена: / Сис.шифр: 84(2Рос=Рус)1-4 / Авт.знак: М 22 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)1-44